Challenges of a digital approach: considerations for an edition of Pedro Homem de Mello’s poetry - Pereira, Elsa (2017)
This presentation elaborates on reasons to adopt an electronic approach to an edition of Pedro Homem de Mello's poetry. More specifically, it focus on the existence of multiple versions of this author’s poems, arguing that structural variance (which results from the process of vertical revision) can best be visualized through an electronic edition, and that the affordances of the medium contribute to reconceiving the concept of text, as a fluid entity that is subject to expansion, through its divergent manifestations. With that in mind, it will present a couple of examples where this kind of variation occurs, and point out a few challenges to going digital.